Interactions between Emotions Detection and Drivers - Shen, Boyu (Transactions on Computer Science and Intelligent Systems Research, 2024)
Nowadays, intelligentized human-machine interactions technologies are developing in a incredible speed, more areas these technologies are applied in. In recent years, intelligent cabins become a main-stream topic which is a tech aims for serving drivers and improving the driving experience. As the trend towards increasingly intelligent vehicles, more scientific researchers put emphasis on researching practical applications which can improve driving experience and satisfaction of drivers and passengers. In this case, intelligent cabins is a main field of these technologies’ applications. In order to offer a better, safer driving experience, some human-computer interaction techniques are applied to cabins for the sake of ensuring the safety of drivers and passengers. As well as improve the driving experience, to enhance the safety and stability during the driving, stabilize the driver’s emotion is a crucial strategy. Emotions can significantly influence the status of drivers and lower the margin of safety. In this case the intelligent cabin can make some adjustments to prevent or eliminate any potential danger. This article wants to analyze some examples that focus on non-intrusive and broadly appealing aspects.